Impact of Gender on Consumers’ Agreeableness on the Structural Ecological Cues in Environmentally Friendly Food Packaging - Lakmali, M.G.T.; Samaraweera, G.C. (University of Jaffna, 2021)
The concept of environmentally friendly packaging is at its initial stage yet in the Sri Lankan context in particular. However, environmental sustainability is the main focus of the world in which the environment is deteriorating terribly at present mainly due to non- degradable packaging. Packaging structural ecological cues referred to the cues that relate to the structure of packaging mainly concerned the reduction of its structure, the quality of packaging materials (recycled, recyclable, from renewable sources), and reusability of the package itself. Since consumer behavior is highly attached to the gender of the consumer and gender is considered as the main demographic factor vital in purchase decision-making by individuals, the main objective of this study was to identify the impact of gender on consumers’ agreeableness on the nature of packaging material used in food products packed in an environmentally friendly manner with special reference to dairy products. A pre tested structured questionnaire was distributed among the consumers visiting the Cargills Food city outlet located at Galgamuwa facing Kurunegala-Anuradhapura main road, Sri Lanka by using a simple random sampling technique (time randomization). The sample size consisted of 104 consumers selected by randomizing time segments during shopping hours. An independent sample t-test was used as the main analyzing technique according to the results; the sample consisted of 82% females and 18% males. There was a significant difference (t (102)=-2.453, p=0.016) between males and females in agreeableness towards the usage of minimum packaging material for eco-friendly packages. Male respondents (M=0.26, SD=0.991) agreed with using minimum packaging material for food products more than their female counterparts' use (M=-0.33, SD=0.944). Therefore, when designing a package for dairy products targeting male consumers, a minimum amount of packaging material should be used as a means of attracting more male consumers towards the product. From the environmental perspective, minimum use of material for food packages leads to lower environmental deterioration and efficient utilization of limited resources. The present findings are important for product/package designers, policymakers, environmentalists in particular.
Keywords: environmentally friendly; gender; packaging; structural ecological cues